2013
DOI: 10.3109/02699052.2012.743185
|View full text |Cite
|
Sign up to set email alerts
|

Serial monitoring of CO2reactivity following sport concussion using hypocapnia and hypercapnia

Abstract: These data suggest that, following mTBI: (1) CVR is not impaired at rest; (2) CVR is impaired in response to respiratory stress; and (3) the impairment may be resolved as early as 4 days post-injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 26 publications
0
74
0
1
Order By: Relevance
“…One study examined the effects of repetitive blows to the head from a career in boxing by using active non-concussed boxers (ie, had not been diagnosed with a concussion recently) who had recently (within the past 72 h) completed a sparring session and compared these results with ‘physical-fitness’ matched non-boxing control athletes (ie, controls who had not engaged in any form of contact sport that may have resulted in head trauma and had not sustained a concussion) 30. The other two studies were primarily comprised of hockey players (85%31 and 90%14). Among the two, one study did not compare results with a control group,31 while the other recruited non-concussed athletes from the same university as the concussed athletes were recruited 14.…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the effects of repetitive blows to the head from a career in boxing by using active non-concussed boxers (ie, had not been diagnosed with a concussion recently) who had recently (within the past 72 h) completed a sparring session and compared these results with ‘physical-fitness’ matched non-boxing control athletes (ie, controls who had not engaged in any form of contact sport that may have resulted in head trauma and had not sustained a concussion) 30. The other two studies were primarily comprised of hockey players (85%31 and 90%14). Among the two, one study did not compare results with a control group,31 while the other recruited non-concussed athletes from the same university as the concussed athletes were recruited 14.…”
Section: Resultsmentioning
confidence: 99%
“…228,229 In human studies, stimulation-induced increases in blood flow have also been shown to be perturbed after TBI. [232][233][234] Data are also available showing that, in addition to the acute changes in CBF, long-term alterations in rCBF are also observed in experimental and clinical models (Fig. 4).…”
Section: Cerebral Blood Flow Alterationsmentioning
confidence: 99%
“…Other studies have found both increases as well as no change when examined within a day or two following injury [64,65]. Studies examining mTBI patients in the acute phase have also found ANS dysfunction such as altered cerebrovascular reactivity [11,66,67], cerebral autoregulation, cerebral oxygenation and heart rate variability [68] when compared to uninjured controls; however, these findings seem to normalize within 4 -14 days post-injury [12,67,68]. Research surrounding these phenomena in PCS patients is, however, somewhat limited.…”
Section: Theory 4: Altered Cerebral Blood Flowmentioning
confidence: 99%